Preparation and Spectroscopic Study of New NS Ligand and its Cd(II) and Zn(II) Metal Complexes - Sadeq, Hamsa Thamer (Al-Nahrain Journal of Science, 2013)
A new nitrogen sulphur Schiff base has been prepared from the condensation 1-(pyridin-4-yl) ethanone with 3-methylbenzyl hydrazinecarbodithioate leading the formation of new ligand 3-methylbenzyl (2Z)-2-[1-(pyridin-4-yl)ethylidene]hydrazine carbodithioate (PE3MBC). The ligand was reacted with Cd(II) and Zn(II) metal salts to form new coordinated complexes. The new ligand and its metal complexes were characterized via various physico-chemical and spectroscopic techniques and conductivity, magnetic susceptibility of metal complexes based on the data analysis the metal complexes are expected to be tetrahedral in geometry.